OPTIMASI PRODUKSI ECOPRINT FABRIC DENGAN TEKNIK ROTARY PRINTING - Cahyana, Agung; Afrizal, Afrizal (Institut Seni Indoensia Surakarta, 2021)
Abstract Ecoprint is a process of transferring colors and shapes to the fabric through direct contact between the leaves and the fabric. Ecoprint technique is an advancement technique in ecofashion that produces environmentally friendly fashion products. The coloring that are often used by the techniques are iron blanket technique and pounding technique. Furthermore, another technique used for coloring ecoprint fabric is using the leaves as ecoprint stamps. It works by coloring the leaf sheet with natural or synthetic dye and followed by adhering the leaf onto the fabric. By pressing the leaves that have been covered in dye, a leaf motif with its tissue will appear on the fabric. The ecoprint stamp technique is easier than other techniques. In the implementation, this technique is still considered taking a long time in the process that an eco-rotary printing technique needs to be developed. Its technique is expected to solve problems that ecoprint stamp techniques have. The engineering of eco rotary print tool as a medium on cap rotary printing technique is resulting 2 prototypes. i.e., 2 roll model, and 3 roll model. The eco-rotary printing method is inspired by a motif roll paint that are able to give color motif on the walls in a relatively fast time. Thus, the leaves are affixed to the roll combined with natural dyes to create a leaf motif on the surface of the fabric. The test results from the two prototypes of the tool are presented. The 3 roll model gives the result of leaf motif color on the fabric with better quality than the 2 roll model. This makes production more effective and efficient in terms of the time of the production process. And, finally, the results of this study are very possible to be utilized in the production of large-scale ecoprint fabric. Key word : Ecoprint, Ecofashion, Eco Rotary Print